HOUT-01. A RETROSPECTIVE ANALYSIS OF OUTCOMES WITH TEMOZOLOMIDE AS INITIAL TREATMENT OF GRADE 2 OLIGODENDROGLIOMA. (5th November 2018) - Morales, Hollie; Homer, Lauren; Langford, Jordan; Maxwell, Amiee; Smith-Cohn, Matthew; Jensen, Randy; Colman, Howard; Cohen, Adam
Abstract: INTRODUCTION: Prior randomized studies have shown a survival benefit of radiation and chemotherapy compared to radiation alone for grade 2 gliomas (astrocytoma and oligodendroglioma) and grade 3 oligodendroglioma. However, data is mixed regarding outcomes for patients treated initially with chemotherapy alone as well as outcomes based on sequence of chemotherapy and radiation treatments. METHODS: We performed a retrospective analysis of outcomes in grade 2 oligodendroglioma treated initially with temozolomide (TMZ) alone. Variables included in the analysis were age, extent of resection, timing of TMZ treatment, progression free survival, and overall survival. RESULTS: A total of 37 patients with grade 2 oligodendroglioma who received TMZ as the first course of treatment were identified. Median age at diagnosis was 43 years. Extent of resection was as follows: complete resection 32%, subtotal resection 43%, stereotactic biopsy 14%, and unknown in 11%. Of the 37 patients in the cohort, 41% received TMZ immediately following initial diagnosis with the remaining 59% receiving TMZ after initial observation. Median PFS after TMZ treatment was 3.94 years, and 25% of patients treated with TMZ alone progressed within 2 years. Despite the high rate of early progressors, the median overall survival with TMZ alone as initial treatment was 15.46 years Extent of resection was not significantly associated with survival. CONCLUSIONS: This retrospective series supports the observations from the TMZ monotherapy exploratory arm of CODEL that PFS in oligodendroglioma patients treated with TMZ alone as initial therapy is likely significantly worse than patients treated with combination of radiation and chemotherapy. The relatively good OS in this same patient population suggests that additional salvage therapy at the time of progression may still result in prolonged survival. Clinical and molecular biomarkers are needed to identify higher or lower risk subtypes within oligodendrogliomas to assist in treatment decision making.